NOISE-INDUCED HEARING LOSS - Cabral Barbosa, Alice; de Oliveira Arantes, Arthur; de Almeida Sousa, Jéssica; Carolina Rios Fonseca, Maria; Mitsue de Castro Matsuoka, Sarah (Health and Society, 2022)
The aim of this article is to elucidate the main aspects of Noise Hearing Loss. Pathology that has been increasing since the Industrial Revolution since the second half of the 18th century. The worker’s health did not go unpunished in the context of a change in mass production: repetitive strain injury, musculoskeletal disorders, definitive or temporary deafness and even psychic suffering are frequent to the work environment. It is essential to emphasize that health is protected by the Occupational Health Legislation, which is the legal framework for states and the city to fulfill their attributions by reducing the area of friction and directing their actions to provide effective promotion, health protection and prevention of injuries related to the labor environment in line with the basic principles of the Unified Health System.